2024
DOI: 10.3389/fimmu.2024.1321395
|View full text |Cite
|
Sign up to set email alerts
|

Role of the intestinal microbiome and its therapeutic intervention in cardiovascular disorder

Ameer Luqman,
Adil Hassan,
Mehtab Ullah
et al.

Abstract: The gut microbiome is a heterogeneous population of microbes comprising viruses, bacteria, fungi, and protozoa. Such a microbiome is essential for sustaining host equilibrium, and its impact on human health can be altered by a variety of factors such as external variables, social behavior, age, nutrition, and genetics. Gut microbes’ imbalances are related to a variety of chronic diseases including cancer, obesity, and digestive disorders. Globally, recent findings show that intestinal microbes have a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 283 publications
0
6
0
Order By: Relevance
“…Beneficial effects of FMT include preserved intestinal barrier function, improved intestinal motility, production of SCFA or a reduced number of pro-inflammatory bacterial strains in the gut [ 181 , 182 , 183 ]. The potential benefit of FMT was reported, e.g., in obesity, cardiovascular disorders, epilepsy and cognitive impairment [ 184 , 185 , 186 , 187 ]. In the animal MPTP model of PD, FMT was shown to improve the composition of the gut microbiota, decrease α-synuclein expression, inhibit microglial activation in SN, block pro-inflammatory signaling pathways and reduce behavioral changes [ 188 , 189 ].…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…Beneficial effects of FMT include preserved intestinal barrier function, improved intestinal motility, production of SCFA or a reduced number of pro-inflammatory bacterial strains in the gut [ 181 , 182 , 183 ]. The potential benefit of FMT was reported, e.g., in obesity, cardiovascular disorders, epilepsy and cognitive impairment [ 184 , 185 , 186 , 187 ]. In the animal MPTP model of PD, FMT was shown to improve the composition of the gut microbiota, decrease α-synuclein expression, inhibit microglial activation in SN, block pro-inflammatory signaling pathways and reduce behavioral changes [ 188 , 189 ].…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…A meta-analysis of nine studies using olive oil supplementation also showed reduced risk of preeclampsia [208]. Increased dietary fiber has consistently shown reduced preeclampsia risk [209] perhaps through the mechanism of improving gut dysbiosis and increasing production of short chain saturated fatty acids [210] [211] [212] . Supplementation of omega-3 fatty acids has had mixed results with initial studies showing no benefit, but a 2018 Cochran meta-analysis showing possible reduction of preeclampsia risk with a relative risk of 0.84 in general population with low quality evidence, but significant protection among women with high risk [213] .…”
Section: Dietary Intervention Studiesmentioning
confidence: 99%
“…Some of the trials on the atheroprotective effects of anti-inflammatory agents are summarized in Table 2. In the conundrum of atherosclerosis there are risk-enhancing factors such as Lp(a) [89,90] and the microbiome [91,92]. Lp(a) seems to be the strongest independent genetic risk factor for myocardial infarction and aortic stenosis [93] and is associated to increased mortality [94].…”
Section: Playersmentioning
confidence: 99%